Studies on Heavy Metal Pollution of Sone River Water - Chauhan, R.P.S.; Suraiya, Afshan; Dwivedi, Dharmendra (Asian Journal of Chemistry, 2016)
In the present investigation the mercury concentration in water and fish samples of different species collected from the river Sone were determined. The levels of mercury range in water were found to be 0.054–0.01, 0.060–0.012, 0.050–0.019 mL/L in summer, monsoon and winter seasons respectively. The concentration of mercury is maximum in Chela-Untrahi while minimum in Labeo-Beata species.